Traffic-Related Air Pollution (TRAP) in relation to respiratory symptoms and lung function of school- aged children in Kuala Lumpur - Suhaimi, Nur Faseeha; Jalaludin, Juliana; Roslan, Nur Intan Shafiqah (Taylor & Francis, 2023)
Traffic-Related Air Pollution (TRAP) exposure has been connected to significant health impacts among children. A cross-sectional comparative study was conducted among school children in Malaysia to determine the relationship between their exposure to TRAP and respiratory health effects. Air monitoring was conducted in schools and residences, while the childrens routines were investigated using a diary of daily activities. Respondents background and respiratory symptoms were obtained from a validated questionnaire, while a spirometry test was performed to determine their lung function status. The distances between schools and residences from the had contributed to the higher concentration of air pollutants in this study, which had associations with the childrens respiratory symptoms and lung function status. PM2.5 was the main predictor influencing the respondents respiratory symptoms and lung function abnormalities. In conclusion, exposure of school children to a high TRAP level might increase their risk of getting respiratory symptoms and lung function reduction.